Gen-Z Sadar Hukum: Edukasi Cegah Kenakalan Remaja Sejak Dini - Ladong, Ar Fani Fanessa; Rahmadani, Suci (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
Juvenile delinquency has become an alarming phenomenon as it not only violates social norms but also carries potential legal consequences. The lack of adolescents’ understanding of legal rules and the social impact of deviant behavior is a major factor behind the prevalence of delinquency among students. To address this issue, thematic KKN students from Hasanuddin University implemented the Gen-Z Sadar Hukum program at SMA Negeri 11 Sidrap with the aim of fostering legal awareness from an early age. The program was designed through school observations and interviews, the preparation of legal education materials covering definitions, factors, types, impacts, and preventive measures of juvenile delinquency, as well as interactive counseling through presentations, quizzes, discussions, and the installation of educational posters. A total of 84 students participated in the activity. Evaluation was conducted using pre-test and post-test assessments to measure students’ level of understanding. The results indicated a significant improvement, with the average score increasing from 38.45 in the pre-test to 67.26 in the post-test, or around 75%. This improvement demonstrates that an educational approach based on active participation is effective in raising legal awareness and preventing deviant behavior. The program contributes to building a legally aware young generation and can serve as a preventive intervention model in other schools.